FAMILY MEDICINE APPROACH BASED ON A WEB-SERIES REVIEW: A CASE REPORT ON HYPEREMESIS GRAVIDARUM - Firnadi, Raden Roro Litiya Parahita Putri; Affianti, Nugraeni; Karimah, Azimatul (Journal of Community Medicine and Public Health Research, 2021)
Family medicine (FM) is a patient-centered and community-based clinical method. The FM has multiple strengths that are useful for medical students, such as provides continuing care to patients and families. Because of the COVID-19, medical students have been removed entirely from the clinical learning environment. Online teaching has played key roles in medical education by covered key clinical conditions, case studies, and examinations. According to the latest American College of Obstetricians and Gynecologists (ACOG), Hyperemesis Gravidarum (HG) is the term for the most severe form of nausea and vomiting of pregnancy. We used the method to collect data for a case report taken from a web-series review on Netflix, titled "Virgin River”, Season 2, Episode 1 to 3. From the symptoms and physical examination of the patient, Ms. CR was diagnosed with HG complicated by dehydration, cardiac arrhythmia, and hypoglycemia. The treatment that has been given to her includes non-pharmacological and pharmacological therapy. The family medicine approach has an important role because it has a strong mutual trust based on the doctor-patient relationship. Also, the family has a significant role in the treatment of patients since it can provide effective psychological and emotional support.